Multiple intelligence assessment in teaching English for young learners - Ernawati Ernawati; Hana Tsurayya; Abdul Rahman A. Ghani (Universitas Negeri Yogyakarta, 2019)
There are many schools in Indonesia that provide English as one of their subjects. English has been taught from elementary schools, even in Kindergarten. Ironically, teaching English in most rural schools still uses a conventional method such as memorizing and translating. Many teachers cannot afford to provide well-designed, meaningful exercises for students to use on a one-to-one learning basis. As a result, students seem not having interest in learning English. Based on this reason, this study was conducted to identify students' intelligence through Multiple Intelligence Assessment to get effective approach in teaching English for young learners. The participants are an English teacher and students at an early childhood education center. This research focuses on presenting a deep description of the Multiple-Intelligence assessment to identify students' intelligence in order to get an effective way of teaching English for young learners. In collecting the data, three instruments were used: observation, interview, and document analysis. The findings of this study show that students have different interests and nature; some students love singing, some others enjoy drawing, and others like role-playing. Multiple-Intelligence Assessment helps the teachers to identify students' interests and bring them building some learning activities to attract them in learning English.